Effectiveness of micro-induction approaches to buprenorphine initiation: A systematic review protocol. (December 2020) - Moe, Jessica; Doyle-Waters, Mary M.; O'Sullivan, Fiona; Hohl, Corinne M.; Azar, Pouya
Highlights: The need to be in withdrawal during standard buprenorphine inductions may be a barrier. Microdosing is a novel method of buprenorphine induction that avoids withdrawal. Our systematic review will assess evidence on buprenorphine microdosing approaches. Abstract: Background: Buprenorphine is first-line opioid agonist therapy for opioid use disorder. Standard regimens require that patients be in opioid withdrawal prior to induction, which is a barrier for many. Micro-induction is a novel induction approach that does not require patients to be in withdrawal. Our primary objective is to synthesize available evidence on the effectiveness of micro-inductions on patient and clinical outcomes compared to standard dosing or other approaches, or evaluated without a comparator group. Secondary objectives are to synthesize evidence on clinical factors that influence micro-induction effectiveness, and to summarize micro-induction regimens described in the literature. Methods: We will search MEDLINE, Embase, CINAHL, Psycinfo, Science Citation Index, and the grey literature for studies that include adolescents or adults with opioid use disorder who received a buprenorphine micro-induction regimen. We will consider any patient or clinical outcomes defined by study authors. We will include controlled and non-controlled interventional studies, observational studies, case reports/series and reports from relevant organizations or guidelines pertinent to our third objective. We will select studies, extract data and assess study quality (using the Downs and Black, and Cochrane Risk of Bias tools) in duplicate. We will narratively synthesize our results, and will meta -analyze outcome measures if multiple studies report common outcomes with acceptably low heterogeneity. Discussion: Our review will include the most up-to-date available data on buprenorphine micro-inductions. We anticipate limitations relating to study heterogeneity and quality. We will disseminate study results widely to inform updated guidelines for opioid agonist therapy prescribers.